2023
DOI: 10.1093/eurheartj/ehad413
|View full text |Cite
|
Sign up to set email alerts
|

Balloon pulmonary angioplasty for chronic thromboembolic pulmonary hypertension: a clinical consensus statement of the ESC working group on pulmonary circulation and right ventricular function

Irene M Lang,
Arne K Andreassen,
Asger Andersen
et al.

Abstract: The current treatment algorithm for chronic thromboembolic pulmonary hypertension (CTEPH) as depicted in the 2022 European Society of Cardiology (ESC)/European Respiratory Society (ERS) guidelines on the diagnosis and treatment of pulmonary hypertension (PH) includes a multimodal approach of combinations of pulmonary endarterectomy (PEA), balloon pulmonary angioplasty (BPA) and medical therapies to target major vessel pulmonary vascular lesions, and microvasculopathy. Today, BPA of >1700 patients has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 108 publications
1
34
0
7
Order By: Relevance
“…[39] Percutaneous transluminal pulmonary artery (PTPA) intervention is a crucial therapeutic approach for inoperable CTEPH and persistent/recurrent PH after PEA. [40] A multicenter study from Poland that included 236 patients with CTEPH showed a 3-year survival rate of 92.4% after initial balloon pulmonary angioplasty (BPA). [41] In patients with TA-PH, the mPAP decreased significantly from 51 to 38 mmHg over an average follow-up of 37 months after PTPA; this group also demonstrated a 3-year survival rate of 93.7%, compared with 76.2% in the non-PTPA group.…”
Section: Treatment Rationale For Cpasmentioning
confidence: 99%
“…[39] Percutaneous transluminal pulmonary artery (PTPA) intervention is a crucial therapeutic approach for inoperable CTEPH and persistent/recurrent PH after PEA. [40] A multicenter study from Poland that included 236 patients with CTEPH showed a 3-year survival rate of 92.4% after initial balloon pulmonary angioplasty (BPA). [41] In patients with TA-PH, the mPAP decreased significantly from 51 to 38 mmHg over an average follow-up of 37 months after PTPA; this group also demonstrated a 3-year survival rate of 93.7%, compared with 76.2% in the non-PTPA group.…”
Section: Treatment Rationale For Cpasmentioning
confidence: 99%
“…The current BPA technique is well documented, 10,17,24 but briefly, vascular access is obtained via the femoral or internal jugular vein. A right heart catheterization is performed to obtain baseline hemodynamics to assess PH severity, and subsequently, a 6F 90-cm sheath is placed into the target pulmonary artery through a series of wire and catheter exchanges.…”
Section: Bpa Techniquementioning
confidence: 99%
“…However, over the last 20 years, balloon pulmonary angioplasty (BPA) has emerged as a viable alternative, and it is now an established class I treatment option in select inoperable CTEPH cases with consensus BPA guidelines recently published. 9,10 In this manuscript, we review the history and evolution of BPA, as well as the landmark studies that have solidified BPA as an integral treatment modality for CTEPH, and how our understanding of the role of BPA in the treatment of CTEPH continues to evolve.…”
Section: Introductionmentioning
confidence: 99%
“…1A,C). 2,4 Her pulmonary hypertension remained severe despite riociguat and ambrisentan (Table 1). The patient was previously turned down for both surgical pulmonary thromboendarterectomy (PTE) and transcatheter intervention at an outside institution due to high risk and unclear benefit in the setting of prior septic emboli.…”
Section: Introductionmentioning
confidence: 99%
“…Workup, including nonselective pulmonary angiography, led to a diagnosis of CTEPH with a type D, ostial CTO in left lower posterior branch (A9 and A10) and a type D, pouch CTO in the right truncus anterior (A1 and A3) (Figure 1A,C). 2,4 Her pulmonary hypertension remained severe despite riociguat and ambrisentan (Table 1). The patient was previously turned down for both surgical pulmonary thromboendarterectomy (PTE) and transcatheter intervention at an outside institution due to high risk and unclear benefit in the setting of prior septic emboli.…”
Section: Introductionmentioning
confidence: 99%